Economie consequences: The relationship between financial reporting and strategic planning, management and operating control decisions* - COVALESKI, MARK A.; DIRSMITH, MARK W.; WHITE, CLINTON E. (Contemporary Accounting Research, 1987)
Abstract. It has long been recognized that financial reporting influences the decisions of external parties interesting in gauging organizational performance. More recently, it has been argued that it may also influence managerial decisions made within the reporting entity. This article examines the relationship between external financial reporting and three levels of decisions made within organizations: operating control, management control, and strategic planning decisions. A review of the accounting literature dealing with stewardship, accountability and information inductance, and selected studies in organizational theory and sociology leads us to hypothesize that financial reporting exerts its strongest influence on strategic planning across four phases of the decision process. Evidence gathered from a case study mode of analysis that entailed distributing a description of a fictitious electronics company operating in a dynamic and complex industry to corporate managers and independent auditors, supports this primary hypothesis. Various implications for managerial decision making, the promulgation of external financial reporting policies, and further research are examined. Résumé. Il est admis depuis longtemps que la publication de l'information financière influence les décisions des tiers intéressés à mesurer la performance d'une organisation. Plus récemment, certains ont affirmé qu'elle peut également influencer les décisions de gestion prises à l'intérieur même de l'entreprise. Cet article étudie la relation entre la publication de l'information financière et trois niveaux de décisions de la firme: des décisions de contrôle d'exploitation, de contrôle de gestion, et de planification stratégique. Un examen de la documentation comptable portant sur l'aspect fiduciaire, sur l'obligation redditionnelle et sur l'information incitative, ainsi que diverses études en théorie organisationnelle et en sociologie, nous amènent à poser l'hypothèse que la publication de l'information financière exerce sa plus forte influence sur la planification stratégique à travers quatre phases du processus décisionnel. Les informations probantes recueillies au moyen d'une étude de cas qui a nécessité la distribution, à des gestionnaires de sociétés ainsi qu'à des vérificateurs, d'une description d'une société d'électronique fictive œuvrant dans un secteur industriel dynamique et complexe, appuient l'hypothèse fondamentale. Sont examinées également diverses conséquences sur les décisions de gestion, la promulgation de politiques relatives à la publication de l'information financière et les possibilités de recherche future.